Pembelajaran Bahasa Inggris Untuk Anak-Anak Di Pondok Pesantren Kanak-Kanak Bayur Desa Barurejo Kecamatan Siliragung Kabupaten Banyuwangi - Zulfi Zumala Dwi Andriani; Ahmad Mufarih Hasan Fadly; Dewi Khawa (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The aims of the program is to introduce English to the community, especially to children. English learning methods and materials used in this program are adjusting to the age of children who are still in elementary school. The materials provided are Alphabets, Numbers, Telling stories. While the learning method used is pictures and games. This program is implemented at the Pesantren for children age in Barurejo Village, Siliragung District, Banyuwangi Regency. Through this program, it is hoped to provide opportunities to practice teaching method for IAI Darussalam students which are accompanied by lecturers, and to build strong friendship between IAI Darussalam and community. The result of the program is some children are very enthusiastic in taking part in learning English, and the caregivers ask the team to provide regular English learning at the Pesantren.